Dynamics of Nepalese Stock Market Performance: An Analysis of Macro-economic, Firm-specific, Size, and Event Factors - Rajesh Gurung (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study examines the multifaceted dynamics influencing the performance of the Nepalese stock market employing time-series ARDL analysis techniques. The study investigates the influence of macroeconomic indicators (gross domestic product, gross domestic savings, interest rates), firm-specific factors (total assets, return on equity), market size (number of listed companies), and event factors (political instability, policy changes) on stock market performance, measured by the stock market index. The ARDL bounds test (F-statistic = 8.378, df = 6, I(0) = 2.88, I(1) = 2.88, α = 1%) indicates the presence of long-run interrelationships among the variables of interest. Additionally, the significant negative coefficient of the error correction term (etc. (-1) = -0.527, p < 0.01) suggests a long-run convergence towards equilibrium. In the short run, political instability exhibits an adverse effect on stock market activities (β = -0.347, p < 0.01), while favorable policy changes demonstrate a positive impact (β = 0.369, p < 0.01). The study emphasizes that authorities and market actors must address the complex linkages of these dynamics impacting Nepal's stock market functioning. It improves the literature on emerging equity markets and informs government and investment decisions in Nepal's fast-changing financial landscape by highlighting stock market performance's many factors.